GAMBARAN POLA MENSTRUASI AKSEPTOR KONTRASEPSI SUNTIKAN 1 BULANAN DAN 3 BULANAN DI PUSKESMAS OEBOBO TAHUN 2011 - BRINGIWATTY BATBUAL (Jurnal Kebidanan: MIDWIFERY MEDICAL JOURNAL, 2014)
Background: Based on interviews by researcher when doing practice in health centers Puskesmas Oebobo to the mother injectable contraceptive DMPA users, from 5 acceptors 4 of them saw that at the time of menstrual time they get spooting, sometimes menstruation but sometimes not, one person stated menstrual period regularly. While the contraceptive acceptors cyclofem that during menstruation menstrual blood remains smooth as usual but one person said that her menstrual blood in the form of spots, sometimes not gettingmenstruationregularly.Objective: to describe menstrual pattern contraceptive injections acceptor monthly (cyclofem) and three monthly (DMPA).Methods: This study is a descriptive study with survey approach. Sampling by quota sampling. Samples injections monthly and three monthly each 30 respondents.Results: The menstrual patterns that often occur at the injection acceptors monthly are menstrual cycles 21-35 days by 28 mothers, menstrual duration of 2-8 days by 30 mothers and 20-80 ml of menstrual blood counts were 21 mothers, who get spotting as many as 27 Mother and menstrual cycles 21-35 days by 25 mothers, menstrual duration of 2-8 days by 30 mothers and blood counts <20 ml were 21 mothers, who get spotting as many as 26 mothers and who experience amenorrhea were 21 mothers.Conclusion: the average in menstrual patterns of contraceptive acceptors cyclofem and DMPA, most of the acceptor contraceptive DMPA amenorrhea compared cyclofem contraceptive acceptors. Most of the acceptors of contraceptive DMPA experience spotting than contraceptive acceptors cyclofem.